PENGARUH FAKTOR PSIKOLOGIS, BUDAYA DAN SITUASIONAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKO ALFAMART DI KECAMATAN NGALIYAN, SEMARANG - Puspitasari, Amarwati -; Taviyastuti, Taviyastuti -; Saleh, Khairu - (Politeknik Negeri Semarang, 2016)
PT Sumber Alfaria Trijaya Tbk is one of thecompanies engaged in modern retail withAlfamart store as stores. Consumer Buyingdecision is one measure that can describe theperformance of the company's existence. Thepurpose of this study is to investigate theInfluence of Psychological Factors, Culturaland Situational to Consumer BuyingDecisions in Alfamart Stores in NgaliyanDistrict, Semarang. To get the appropriateresults, this study uses Statistical methodssuch as multiple linear regression method, Ttest, F test and the coefficient ofdetermination (R2). Based on the results ofmultiple linear regression equation Y = 1.673+ 0.227 (X1) + 0.263 (X2) + 0,305 (X3) .Based on the the analysis t value of variablepsychological factors is (2.404), culturalfactors is (2.901) , situational factors is(4.480) having a value greater than t table(1.660) . ANOVA calculation results areknown that the calculated F value (40.980) isgreater than F table (2.700). Then it can beconcluded that these three variables partiallyand simultaneously influence purchasingdecisions. And situational factors (X3) havestrong dominant influence on purchasingdecisions.